Fabrication and photocatalytic activity of LaFeO3 ribbon‐like nanofibers. Issue 6 (19th December 2019) - Li, Shudan; Guo, Meiling; Wang, Xiuhua; Gao, Kun
Abstract: LaFeO3 ribbon‐like nanofibers were synthesized via a sol–gel‐assisted electrospinning method. The differences in morphology and photocatalytic property of LaFeO3 nanofibers prepared through different needles were investigated. At the same time, the morphology and photocatalytic activity of porous LaFeO3 nanobelts formed at different calcination temperatures were also investigated. Scanning electron microscopy results revealed that the obtained ribbon‐like LaFeO3 nanofibers made using a coaxial needle contained a large number of pores. Moreover, with the increase of calcination temperature, the morphology of the fibers also changed. X‐ray diffraction analysis showed a series of fibers all in orthorhombic LaFeO3 phase but no other impurities. In addition, the photocatalytic activity of LaFeO3 nanofibers was studied for the degradation of methylene blue under visible light. The results demonstrated that ribbon‐like nanofibers exhibited excellent photocatalytic activity compared with the others and the LaFeO3 nanobelts calcined at 500°C had the best photocatalytic activity. Based on the experimental results, possible forming mechanisms involving in LaFeO3 nanofibers through different needles are also discussed. Abstract : LaFeO3 ribbon‐like nanofibers were synthesized via a sol–gel‐assisted electrospinning method. The differences in morphology and photocatalytic property of LaFeO3 nanofibers prepared through different needles were investigated. At the same time, the morphology and photocatalytic activity of porous LaFeO3 nanobelts formed at different calcination temperatures were also investigated. Possible forming mechanisms involving in LaFeO3 nanofibers through different needles were also discussed.